2018
DOI: 10.1097/pec.0000000000000810
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Intranasal Fentanyl Versus Intravenous Morphine for Abscess Incision and Drainage

Abstract: In a small sample of children aged 4 to 18 years undergoing abscess I&D, IN fentanyl was noninferior, and potentially superior, to IV morphine for reducing procedural pain and distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…To determine non-inferiority of coadministered compared with preadministered lidocaine, we used a predetermined margin of non-inferiority (Δ) of 1.80 (SD 2.25). This margin was based on pooling effect estimates from previous randomized clinical trials of children undergoing painful procedures and selecting an estimate that represented a clinically significant difference [14][15][16][17][18]. To demonstrate non-inferiority with this Δ with a 1-tailed α of .025 and power of 80%, we required 25 patients in each arm, for a total of 50 patients.…”
mentioning
confidence: 99%
“…To determine non-inferiority of coadministered compared with preadministered lidocaine, we used a predetermined margin of non-inferiority (Δ) of 1.80 (SD 2.25). This margin was based on pooling effect estimates from previous randomized clinical trials of children undergoing painful procedures and selecting an estimate that represented a clinically significant difference [14][15][16][17][18]. To demonstrate non-inferiority with this Δ with a 1-tailed α of .025 and power of 80%, we required 25 patients in each arm, for a total of 50 patients.…”
mentioning
confidence: 99%
“…This review was performed based on those eight articles. [35][36][37][38][39][40][41][42] Included studies were published between 1999 and 2018, and were conducted in Australia (n=4), United State (n=2), and the United Kingdom (n=2). All included studies contained two comparison arms.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Intranasal fentanyl provided similar levels of behavioral distress and reduced pain levels after abscess incision and drainage procedures of children compared with those receiving intravenous morphine. 12 Similarly, a Cochrane review of pediatric trials indicated that intranasal fentanyl is likely effective for acute moderate-to-severe pain. 13 In addition to evidence indicating efficacy and tolerability of intranasal fentanyl in children, additional research has cited similar effects in adults.…”
Section: Introductionmentioning
confidence: 99%